-18x+25x-12x=

Simple and best practice solution for -18x+25x-12x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -18x+25x-12x= equation:


Simplifying
-18x + 25x + -12x = 0

Combine like terms: -18x + 25x = 7x
7x + -12x = 0

Combine like terms: 7x + -12x = -5x
-5x = 0

Solving
-5x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Divide each side by '-5'.
x = 0

Simplifying
x = 0

See similar equations:

| 43=3d+9 | | -0.6+(-4a)=-14 | | -18-6x+5y=0 | | y=9y-19 | | y=9y-9 | | (1+y)*dx-(1+x)dy=0 | | 8n^2-18n+10=0 | | 4x+0.75=x+x+x+0.75 | | 4x^2-12z+9=0 | | -24.6= | | 8n^2-18x+10=0 | | 20y+5=500-5y | | -0.2+100=y | | 2x-3x+10=0 | | 10x-0.5=8x-15 | | 3(x-1)-2x+5=4(x-2)+4 | | 4s-11=41 | | -0.2p+100=-0.25+0.05p | | -y=-9-3x | | 25=b-9 | | 9-b=29 | | 3x-11=52 | | 36y^2+16=0 | | 8y-15=41 | | -7+6-20-(-8)= | | -5x+9=4x-54 | | (12+3+5k)6+4k+2(k+5)= | | Y+.15=11 | | (-2y)-3y+8=8-5y-12 | | 12+3y=7x | | -0.2p+100=y | | 4(2y-3)=2(3y-2) |

Equations solver categories